Consistency & color stability of catsup from saba (Compressa blanco Teodora) banana - Lafuente, Estelita C.; Gatchalian, Miflora M. (1973.)
ABSTRACT Rare-ripe and fully ripe saba (Compresa blanco Teodoro) variety of bananas were used as base raw materials for banana catsup. Consistency and color stability of the catsup were studied relative to its component and length of storage time. For both the raw materials and the finished products, color, pH, titrable acidity, soluble solids and starch content were analyzed. The finished product was also evaluated by a trained sensory panel of judges. Results of chemical tests and subjective evaluations indicated that the best raw materials in the manufacture of banana catsup would be those from fully ripe "saba" bananas. Color of banana catsup was stabilized even after one month's storage by using McCormick brand of FD & C Red and Yellow dyes at 0.65% and 0.70% concentrations, respectively and mixed with a puree blend at a pH range of 4.0 - 4.3. Separation and/or synthesis of the banana catsup during storage at room temperature was prevented by the incorporation of 0.13% gum tragacanth in the puree. Gum tragacanth at 0.13% did not significantly affect the color, flavor and texture of the product as compared with the control, although it was found to definitely improve the stability of the puree consistency.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Banana products -- Philippines; Ketsup